Measuring Social Return on Investment: Lessons from the Kelas Berbagi (Sekolah Lestari Berbasis Teknologi) CSR Program of PT Pertamina Hulu Energi Jambi Merang - Tasmat, Djulianto; Afrianto; Krisnanto, Yoseph Tri; Wijanarko, M Arif Suryo; Ananda, Fatika Hastigerina; Nofadila, Tefy (Global Writing Academica Researching and Publishing, 2024)
This article aimed to determine the Social Return on Investment (SROI) value in the Kelas Berbagi (Sekolah Lestari Berbasis Teknologi) CSR Program of PT Pertamina Hulu Energi Jambi Merang. This article employed the SROI method. Data collection techniques included interviews and literature studies. Validity tests were conducted through data triangulation obtained from various sources. This research was located in Mekar Jaya Village, Bayung Lencir District, Musi Banyuasin Regency. The results of the study indicate that: 1) SROI calculation needs to be carried out to encourage continuous innovation and improvement in the Kelas Berbagi Program; 2) The Kelas Berbagi Program obtained an SROI value of 2.16; 3) An SROI value of 2.16 indicates a positive value of the social investment made by the company. Moreover, the involvement of stakeholders, including agencies, the government, and community institutions in Musi Banyuasin Regency in the Kelas Berbagi Program illustrates participatory and collaborative cooperation, thus being able to promote environmental knowledge enhancement among the program’s beneficiaries.